ESTIMASI KANDUNGAN UNSUR HARA KALIUM DAN MAGNESIUM PADA TANAMAN NANAS (Ananas comosus (L) Merr.) Menggunakan Unmanned Aerial Vehicle (UAV) DI PT. GREAT GIANT PINEAPPLE - Lukman Mei Widitya; S Sudarto; Aditya Nugraha Putra; Dwi Okiyanto (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Central Lampung is one of the areas that produce a lot of pineapple. Pineapple plants require potassium and magnesium nutrients to produce optimal fruit. The apparent appearance of chlorotic symptoms due to nutrient deficiency of potassium and magnesium makes it possible to be detected using aerial photographs. This study aimed to compare between Green Normalized Difference Vegetation Index (GNDVI), Normalized Difference Vegetation Index (NDVI) and spectral values for predicting potassium and magnesium contents in pineapple plants. The result of regression test showed that GNDVI had the best relationship than NDVI and spectral values. The equation for predicting the potassium nutrient in pineapple plant was with the formula: K=3,342-1,501(GNDVI) with RMSE value 0,1634. The Estimation magnesium in pineapple plants, NDVI had a better relationship with magnesium than with GNDVI and spectral values. The equations for magnesium estimation in plants with NDVI were obtained by using the regression test, i.e.: Mg=0,083+0,288(NDVI) with RMSE of 0,0342. Paired T-test values of GNDVI with potassium (-1,007) and NDVI with magnesium (-1,048) showed that t count was smaller than t table (2,015) and the significance value of both was greater than alpha (Î± = 0,05). So it can be said that the value of estimation with the actual value in the field has no difference that significant.